Book Review. Resurrecting Kuntowijoyo's Idea on Prophetic Transformative (Sosial) Sciences - Harto Wicaksono (Humaniora, 2016)
Understanding Kuntowijoyo’s idea about prophetic (social) sciences was the underpinning for Ahimsa-Putra to produce his lastest work. The fundamental structure of science offered by Kuntowijoyo, according to Ahimsa-Putra, still leaves some problems, both from paradigm aspect and some concepts used in an attempt to apply prophetic social sciences. That is, the idea is not yet ready to be applied into social sciences.This problem arises neither because Kuntowijoyo is not communicative, nor as an indication of the unproductiveness of contemporary scholars to respond to the idea.